2019
DOI: 10.1177/0192513x19894366
|View full text |Cite
|
Sign up to set email alerts
|

Coparenting across the Deployment Cycle: Observations from Military Families with Young Children

Abstract: Contemporary service members and their partners have adapted their coparenting to respond to the specific transitions and disruptions associated with wartime deployment cycles and evolving child development. This qualitative study draws upon interviews with service member and home front parents of very young children to characterize their coparenting experiences throughout the deployment cycle. Parents described varied approaches as they considered their children’s developmental capacities, the fluidity of dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 35 publications
2
27
0
Order By: Relevance
“…of very young children (see DeVoe et al, 2019). Researchers have described the middle phases of the cycle of deployment as sustainment that is characterized by more stability and regularity than other deployment phases (Logan, 1987).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…of very young children (see DeVoe et al, 2019). Researchers have described the middle phases of the cycle of deployment as sustainment that is characterized by more stability and regularity than other deployment phases (Logan, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…Although many military spouses play a critical role in maintaining family life during deployment and transitions/adjustments of reintegration after the service member returns home, managing the deployment cycle for spouses who are parents presents additional and unique challenges (see DeVoe & Ross, 2012 for a detailed description). During deployment, parenting and coparenting responsibilities are highly dependent upon spouses or at-home caregivers for parenting support and assistance (DeVoe, Ross, Spencer, Drew, & Jacoby, 2019). Establishing child care and household routines, communicating with the deployed parent, and managing finances are often exhausting and contribute to the cumulative stress burden among at-home caregivers (Kelley et al, 2001; Lapp et al, 2010).…”
Section: Challenges To Parenting During the Deployment Cyclementioning
confidence: 99%
See 1 more Smart Citation
“…At reintegration, the cumulative pile up of stressors (McCubbin & Patterson, 1983) during deployment separation may not necessarily be alleviated. Athome parents have reported that both negotiating new and resuming previous parenting roles and relinquishing responsibilities taken on during deployment are challenging aspects of reintegration, regardless of a service member's health or mental health status (DeVoe et al, 2019;Knobloch & Theiss, 2011). DRS has been associated with higher levels of mental health symptoms in parent samples (Gibbs et al, 2008;Hisle-Gorman et al, 2015;Rentz et al, 2008).…”
Section: Author Manuscriptmentioning
confidence: 99%
“…For example, during military-related family separations (e.g., due to deployment, non-local military-related training, etc. ), the at-home parent may experience a range of difficult emotions, including fear, anxiety, loneliness, and frustration related to a variety of stressors such as increased responsibilities in the home, temporary loss of a co-parent, and worry about their partner’s safety [ 11 ]. Increased psychological distress may render the at-home parent less able to support their child in the midst of the child’s own worry about their deployed parent and stress associated with separation from an attachment figure [ 12 ].…”
Section: Introductionmentioning
confidence: 99%